PKM Peningkatan Manajemen Usaha Pada UMKM Nila Banjar Indah - Elmiwia Rani Baturante; Achmad Syamsu Hidayat; Leila Ariyani Sofia; Erma Agusliani; Irma Febrianty; Rina Mustika; Muhammad Adnan Zain; Bahruddin Yusuf (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
Good business management plays a crucial role in ensuring the sustainability of a business, whether micro, small, medium, or large scale. However, the reality in the field is that many business actors still do not know how to manage their business properly, as is the case with the Nila Banjar Indah MSMEs. This MSMEs is one of the groups that cultivates and breeds tilapia in Banjar Regency and is a partner in the Community Service program. The Community Service program was conducted using counseling and evaluation methods. The presentation of material on how to group types of costs and how to analyze business feasibility using an LCD and concluded with a discussion between the community service team and the torch target. In the evaluation activity, the results of the initial assessment showed that the average knowledge of the torch target about business management was 33.5%. Meanwhile, the average response value of the partner group after the activity was 74.5%. Based on the results of the t-test analysis, there was a difference in the knowledge of the torch target before and after the counseling (0.00 <0.05).